خبر الآحاد عند الأصوليين و أثره الفقهي - جغوبي, ابراهيم (University of Eloued جامعة الوادي, 2017)
خبر الآحاد عند الأصوليين و أثره الفقهي من بين اهم الموضوعات التي شغلت فكر أهم الأصوليين و الفقهاء قديما و حديثا قضية الاحتجاج بخبر الآحاد ومدى قبوله ، و قد ثارت مسائل فقهية أصولية عديدة مست جانبا مهما من هذه الدراسة لكون ان التناقض الذي تضاربت فيه الآراء و اختلفت فيه المشارب صب حول مدى قبوله من رده لدى الاصوليين في حالة التعارض مع بعض الاصول خاصة ما تعلق منه بعموم البلوى ، كما ثار نقاش مستفيض حول مدى اعتبار خبر الآحاد مصدرا واصلا يعتمد في المسائل الفقهية الهامة كالحدود و الفتوى ، و اذ اننا نجد ان معظم الاصوليين يعتبرون خبر الآحاد مصدرا واصلا لكن مناط الاختلاف الذي رامته هذه الدراسة ، هو بيان جملة الاختلافات التي جعلت من هذا المضوع ذا قيمة علمية و اصولية بدرجة هامة ومن المؤكد ان ذلك الاختلاف مرده تعدد القراءات و الدراسات الفقهية و الأصولية التي تروم البحث الحثيث عن الطبيعة الحقيقية لخبر الآحاد و علاقته بمسائل الفقه عموما و بالشريعة الاسلامية .وقد أدى ذللك الى كثير من الاختلافات في الأصول خاصة المالكية الذين يعتبرون عمل أهل المدينة أصلا من أصولهم لأنهم اعتبروا عمل أهل المدينة عملا متواترا بحكم أنهم مجمعون على العمل به و هذا ليس في سائر الأزمان وإنما في عصر الصحابة والتابعين لاتصالهم المباشر بعهد النبوة أما البقية من الأصوليين فقد اختلفوا في حد التواتر وتعريفاته وتصنيفاته ،فمنهم من رد خبر الآحاد خصوصا إذا تعارض مع القياس كالحنفية مثلا مع العلم أن خبر الآحاد تنبني علية جل الأحكام الشرعية ولكن ردوه لاعتبارات ونصوص أدت عدم العمل به من ناحية الطريق الذي وصلنا به وخاصة الآيات والأحاديث الدالة على التثبت في الخبر بأكثر من واحد. The news of the atheists and the fundamentalist jurisprudence Among the most important topics that occupied the thought of the most fundamentalists and jurists in the past and recently the issue of protesting the news of atheism and the extent of acceptance, and has raised many fundamental doctrinal issues touched an important aspect of this study because the contradiction in which the conflicting views and disagreed in the stripes poured on the acceptability of His response to the fundamentalists in the case of conflict with some of the assets, especially what is related to the general Balwa, and there was a great debate about the extent of the news of atheism is a source of origin depends on important jurisprudential issues such as limits and fatwa, as we find that most fundamentalists consider the news of atheists a source of origin, The difference highlighted in this study, e And the statement of the differences that have made this subject of scientific value and fundamentalism to an important degree and certainly that difference is due to the multiplicity of readings and studies of jurisprudence and fundamentalism, which aims to search diligently about the true nature of the story of atheism and its relationship to issues of jurisprudence in general and Islamic law. To many differences in assets, especially the Maalikis, who consider the work of the people of the city originally of their origins because they considered the work of the people of the city a frequent work because they are gathered to work and not at all times but in the era of companions and followers of their direct connection to the era of prophecy and the rest of the fundamentalists They differed in frequency, definitions and classifications. Some of them responded to the news of the individual, especially if it contradicted with the measurement, such as the faucet, for example, knowing that the news of the atheists is based on most of the shar'i rulings, but they responded to the considerations and texts that led to its failure to work in terms of the way we arrived, Verification of the news more than one.
مذكرة ماستر تخصص اصول فقه
Keywords: :...الخبر- الواحد- الأصوليين- الفقه- الأثر; fundamentals-one –announcements fiqh-effects